The Nature of Zakat in Islamic Law - Heri Siswan (ISNU Nine-Star Multidisciplinary Journal, 2024)
Zakat is one of the pillars of Islam that must be carried out by Muslims as a form of worship that has social and economic goals, such as purifying wealth and helping the poor. In Islamic law, zakat has a strong foundation and is an individual and collective obligation. However, understanding the nature of zakat from an Islamic legal perspective is often hampered by unclear implementation and varying interpretations. This study aims to examine the nature of zakat in Islamic law, both in terms of concept, legal basis, obligations, and its impact on the socio-economic life of Muslims. This study uses a normative legal research method with an approach to Islamic legal sources, such as the Qur'an, Hadith, and the opinions of scholars. The results of the study show that zakat has a very important role in achieving community welfare and strengthening social solidarity, which is reflected in the obligation of zakat regulated in Islamic law. In addition, the proper implementation of zakat can reduce social inequality and advance the economy of Muslims. The conclusion of this study is that zakat is an obligation that is inseparable from Islamic teachings and has major implications for the socio-economic life of Muslims.